López Portillo y Carazo Odio: el apoyo al sandinismo. 1976-1979 - Martínez-Acosta, Hugo (2017)
This article I approaches the Mexican policy in regard to the Nicaraguan revolution during the first years of José López Portillo’s presidency. It also analyzes the meeting points between López Portillo and his Costa Rican counterpart, Rodrigo Carazo Odio, who provided open support for the struggle of the Sandinista National Liberation Front against Anastasio Somoza Debayle, in Nicaragua. Mr. Carazo managed to convey that empathty to Lopez Portillo who became a supporter of the Sandinista revolutionary struggle in various ways.